Women in urban poverty: qualitative look at coping strategies - Tilki, Makbule Evrem. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
This study aimed to conduct a qualitative research on the problems and coping strategies of the women living in urban poverty. Ten Kurdish women (20-35 years old) who lived in Tarlabaşı; one of the inner city slums of Istanbul, were interviewed and the data was analyzed using Grounded Theory (Strauss and Corbin, 1998). The results showed that the women were faced with emotional distress related with deep poverty conditions and adaptation problems related with involuntary migration. The emergent themes also depicted the way they fell outside the social life as a result of their ethnic and cultural backgrounds as well as gender roles that they grow up in. Related with the lack of personal and social resources, they used emotional coping strategies; the ones who could benefit from both emotional and problem focused coping strategies were the ones who had the chance to reach support mechanisms that enriched their resilience capacities.
Keywords: Women -- Turkey.; Women -- Economic conditions.; Urban women -- Turkey.; Poor women.